Relationship Between Cement Distribution Pattern and New Compression Fracture After Percutaneous Vertebroplasty - Tanigawa, Noboru; Komemushi, Atsushi; Kariya, Shuji; Kojima, Hiroyuki; Shomura, Yuzo; Omura, Naoto; Sawada, Satoshi (American journal of roentgenology (1976), 2007)
The objective of this study was to prospectively investigate relationships between cement distribution patterns and the occurrence rates of new compression fractures after percutaneous vertebroplasty. Percutaneous vertebroplasty was performed for osteoporotic compression fractures in 76 consecutive patients. Patients were divided into two groups according to the cement filling pattern shown on radiography and CT: cleft pattern group (group C, n = 34), compact and solid cement filling pattern in vertebrae; and trabecular pattern group (group T, n = 42), sponge-like filling pattern. A visual analog scale (VAS) was used to assess pain severity, and anterior and lateral radiographs of the thoracic and lumbar vertebrae were obtained 1-3 days and 1, 4, 10, 22, and 34 months after percutaneous vertebroplasty. Differences in treatment efficacy and the occurrence rates of new compression fractures were examined and compared for both groups using the Mann-Whitney U test and chi-square test. A significant difference was seen between groups with respect to the volume of cement injected per vertebra (mean volume: group C, 4.5 mL; group T, 3.7 mL; p = 0.01). VAS improvement did not differ significantly between group C (4.6) and group T (4.5). The mean follow-up period was 19.5 months, during which new compression fractures were significantly more frequent in group C (17 of 34 [50%]) than in group T (11 of 42 [26.2%]; p = 0.03). Although cement distribution patterns do not significantly affect initial clinical response, a higher incidence of new compression fractures is seen in patients with treated vertebrae exhibiting a cleft pattern.